Glyoxalase 1 Confers Susceptibility to Schizophrenia: From Genetic Variants to Phenotypes of Neural Function - Yin, Jingwen; Ma, Guoda; Luo, Shucun; Luo, Xudong; He, Bin; Liang, Chunmei; Zuo, Xiang; Xu, Xusan; Chen, Qing; Xiong, Susu; Tan, Zhi; Fu, Jiawu; et al. (Frontiers in Molecular Neuroscience, 2021)
This research aimed to investigate the cause of glyoxalase 1 (Glo-1) to the susceptibility of schizophrenia. Here, significant differences in Glo-1 mRNA expression (P = 3.98 E-5) and enzymatic activity (P =1.40E-6) were found in peripheral blood of first-onset antipsychotic-naïve schizophrenia patients and controls, the following receiver operating characteristic (ROC) curves analysis showed that Glo-1 could be able to predict the schizophrenia risk (P = 4.75 E-6 in mRNA, P = 1.43 E-7 in enzymatic activity, respectively). To identify the genetic source of Glo-1 risk in schizophrenia, polymorphisms of Glo-1 were genotyped by SNaPshot technology in 1069 schizophrenia patients and 1023 healthy individuals. Significant differences were found in distributions of genotype (P = 0.020) and allele (P = 0.020) in rs1781735, in which G >T mutation showed significantly reduction in promoter activity of Glo-1 (P = 0.016). In peripheral blood of first-onset antipsychotic-naïve schizophrenia patients and healthy controls, TT genotype was associated with lower mRNA expression and enzymatic activity compared to GG genotype (P < 0.05). Then basing on the expression quantitative trait locus (eQTL) and functional magnetic resonance imaging (fMRI) analysis, TT genotype of rs1781735, associated with lower RNA expression in brain, showed decreased neuronal activation in left middle frontal gyrus in schizophrenia (P < 0.001). This study for the first time investigated the Glo-1 effect in the schizophrenia risk on multiple levels, from genetic variants, transcription, expression, protein function, all the way to phenotypes.